A rating scale for the severity of Guillain‐Barré syndrome. (14th June 2017) - Guan, Z.; Shang, L.; Zhang, W.; Guo, Y.; Xue, Y.; Li, X.; Gong, Y.; Liu, X.
Abstract : Introduction: The objective of this study was to develop a rating scale to assess the severity of Guillain‐Barré syndrome (GBS). Methods: The preliminary rating scale, which contained 11 items, was developed by the Delphi method, and data of 258 patients were collected to evaluate it. Item analysis was accomplished by 100 patients; the additional 158 patients were used to evaluate the reliability, validity, and discriminative ability of the rating scale. The structure of the rating scale was testified by the confirmatory factor analysis and also made a further evaluation by the correlation analysis. Results: The rating scale contained 10 items. The three factors mainly generalized the motor function, cranial nerve function and autonomic function. The results of reliability and validity showed that the structure of the rating scale was good (χ 2 =68.25, df =32, χ 2 / df =2.13, normed fit index (NFI)=0.919, non‐normed fit index (NNFI)=0.936, comparative fit index (CFI)=0.96, a root mean square error of approximation (RMSEA)=0.085), and the Cronbach's α coefficient for the scale was .852, with the three dimensions ranging from .585 to .752. Conclusion: Reliability and validity of the rating scale are all satisfied. The scale contained the main clinical presentations of GBS, and it is suitable to evaluate the severity of GBS.